2009
DOI: 10.1152/ajpregu.00036.2009
|View full text |Cite
|
Sign up to set email alerts
|

Loss of M2muscarinic receptor function inhibits development of hypoxic bradycardia and alters cardiac β-adrenergic sensitivity in larval zebrafish (Danio rerio)

Abstract: Fish exposed to hypoxia develop decreased heart rate, or bradycardia, the physiological significance of which remains unknown. The general muscarinic receptor antagonist atropine abolishes the development of this hypoxic bradycardia, suggesting the involvement of muscarinic receptors. In this study, we tested the hypothesis that the hypoxic bradycardia is mediated specifically by stimulation of the M(2) muscarinic receptor, the most abundant subtype in the vertebrate heart. Zebrafish (Danio rerio) were reared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
1
29
1
Order By: Relevance
“…The dose of 0.05 mg ml −1 of MS-222 was chosen because it was the lowest dose able to keep the larvae immobilized. Other studies have shown that high doses of MS-222 decrease f H in zebrafish larvae; however, the concentration used in this study is lower than that used in those studies (Steele et al, 2009(Steele et al, , 2011. Furthermore, in our own experiments only a dose of MS-222 above 0.12 mg ml −1 caused a decrease in f H after 10-15 min exposure of 4 dpf larvae.…”
Section: Injection Of Ho-1 Morpholinocontrasting
confidence: 62%
See 1 more Smart Citation
“…The dose of 0.05 mg ml −1 of MS-222 was chosen because it was the lowest dose able to keep the larvae immobilized. Other studies have shown that high doses of MS-222 decrease f H in zebrafish larvae; however, the concentration used in this study is lower than that used in those studies (Steele et al, 2009(Steele et al, , 2011. Furthermore, in our own experiments only a dose of MS-222 above 0.12 mg ml −1 caused a decrease in f H after 10-15 min exposure of 4 dpf larvae.…”
Section: Injection Of Ho-1 Morpholinocontrasting
confidence: 62%
“…In larval zebrafish, the onset of cardiac control via the parasympathetic and sympathetic nervous systems (or circulating catecholamines) is evident as early as 4 dpf (Steele et al, 2009(Steele et al, , 2011. The development of bradycardia in the face of chronic hypoxia in zebrafish larvae is mediated by cardiac muscarinic receptors (Bagatto, 2005) of the M 2 sub-type (Steele et al, 2009), while the tachycardia response to acute hypoxia is probably controlled by a release of inhibitory vagal tone or stimulation of adrenergic receptors by elevated circulating catecholamine levels or catecholamines released from sympathetic neurons (Steele et al, 2009(Steele et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although hypoxic bradycardia was observed in 4 d.p.f. larvae in at least two studies (Bagatto, 2005;Steele et al, 2009), there are also reports of the zebrafish heart being unresponsive to hypoxia until 30 d.p.f. at which time bradycardia develops (Barrionuevo and Burggren, 1999), or actually exhibiting tachycardia (Jacob et al, 2002).…”
Section: The Cardiac Response To Hypercapniamentioning
confidence: 99%
“…Previous studies have also reported a lack of an effect of atropine on resting heart rate until about 12 d.p.f. (Schwerte et al, 2006;Steele et al, 2009), suggesting that parasympathetic cholinergic tone is absent until ~12 d.p.f. However, Hsieh and Liao (Hsieh and Liao, 2002) reported a significant reduction in heart rate in 3 d.p.f.…”
Section: Hypercapnic Tachycardia Is An Adrenergic Reflexmentioning
confidence: 99%
“…Because early life stage (ELS) is one of the most sensitive life stages to toxicity during the life cycle, ELS tests with fish species are commonly used as routine toxicity tests in risk assessment (OECD 1998;Roex et al 2002). D. rerio was recommended as a model fish species for short-term embryo-larval toxicity testing (OECD 1998), and there are many studies investigating the effects of hypoxia on zebrafish embryo or larvae (Padilla and Roth 2001;Ton et al 2003;Rombough and Drader 2009;Steele et al 2009;Van Rooijen et al 2009;Yaqoob et al 2009). We found that the 7-day-old F 3 vhb transgenic larvae may be suitable for study of the hypoxia tolerance traits.…”
Section: Discussionmentioning
confidence: 99%